SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI MA AL FATAH KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Akmalul Iman (UNISAN JURNAL, 2024)
This study uses a qualitative approach that is descriptive in nature, that is, the researcher only describes, analyzes phenomena, events and activities carried out related to academic supervision carried out by the head of MA Al Fatah Natar with data collection techniques through: (1) Observation (2) In-Depth Interviews , and (3) Documentation Study. As for the selection of research informants, using a purposive technique combined with Snowball Sampling. The data collected through the three techniques were then checked for validity by means of triangulation. Then analyzed by: (1) data reduction, (2) data presentation and (3) drawing conclusions. Based on the results of the research, it can be concluded that the findings are as follows: (1) The academic supervision program for the head of MA Al Fatah Natar was prepared based on the results of the analysis of supervision and monitoring of the previous learning process; The school principal’s academic supervision program is prepared at the beginning of the school year, by first identifying problems, setting goals and determining the implementation time, involving the deputy head of curriculum, the deputy head of quality assurance, and the teacher; and carried out systematically, (2) The strategy for implementing the school principal’s academic supervision includes: supervising learning tools, Supervision with class visit techniques, and observation of teacher activities in class, and Implementation of follow-up on the results of academic supervision in the form of personal and group coaching. (3) The implications of the principal’s academic supervision are: (a) Increasing the ability of teachers to develop learning tools (b) Increasing the ability of teachers to carry out the learning process, (c) Increasing the ability of teachers to evaluate student learning outcomes. Conclusion: academic supervision is one way to increase teacher professionalism in planning, carrying out the learning process and evaluating student learning outcomes in order to improve the quality of learning so that both local and national educational goals can be achieved. Keywords : academic supervision, learning quality